The Role of Corporate Governance in Corporate Human Development Disclosures - Nina Febriana Dosinta; Fariastuti Djafar; Nella Yantiana (Universitas Syiah Kuala, 2022)
Objective – The urgency of this research is to examine the effect of corporate governance on corporate human development disclosures.Methodology – This study focuses on corporate reporting by twenty-six Regional Development Banks in Indonesia. It encompasses the examination of annual and stand-alone sustainability reports spanning from 2014 to 2021. Additionally, panel data analysis is employed in this research, specifically utilizing the Fixed Effect Model as the chosen analytical approach.Results – This research result shows that independent commissioners and female directors, as part of corporate governance, have a significant and positive effect on corporate human development disclosures.Research Implications – The implication of this research argues that independent commissioners and female directors, as part of corporate governance, have capabilities that can optimize corporate human development disclosures. By optimizing corporate human development through effective reporting practices, Regional Development Banks can better fulfill their role as agents of development. Principals and agencies must support each other in optimizing corporate human development. Novelty/Originality - The level of disclosure is measured based on the corporate human development index with an agency and human capability theory approach. Disclosure of the corporate human development index is voluntary and reflects corporate welfare through items from the human development index.